An Unusual Case: Pruritic Vulvar Syringoma - Mehmet Dolanbay; Mehmet Serdar Kütük; Semih Uludağ; Mahmut Tuncay Özgün; Ayça Nazlı BULUT; Turhan Ökten (Gynecology Obstetrics & Reproductive Medicine)
Vulvar pruritus and pain are common symptoms for visiting a gynaecologist. A 37-year-old woman presented with a six months history of vulvar papular pruritic lesion unresponsive to topical antifungal and anti-inflammatory therapy. Cutaneous examination of vulva showed multiple, bilaterally, 1-4 mm sized, skin-colored papules over the labia major. Histopathological examination revealed syringoma. She was treated with mild potent corticosteroid cream and oral antihistaminics. Pruritus was improved within two weeks but cutaneous papules were not. Though very rare, vulvar syringoma should be kept in mind in the differential diagnosis of persistent and severe vulvar pruritus.